Jetzt. : Künste in Deutschland heute. (Köln : Kunsthalle, 1970)
Antes, Horst ; Asmus, Dieter ; Bandau, Joachim ; Beuys, Joseph ; Birgfeld, Detlef ; Boldt, Rainer ; Brehmer, KP ; Buthe, Michael ; Costard, Hellmuth ; Farocki, Harun ; Geiger, Rupprecht ; Hauser, Erich ; Kappes, Kurt ; Lohaus, Bernd ; Mack, Heinz ; Mon, Franz ; Nekes, Werner ; Piene, Otto ; etc.
Jetzt. Künste in Deutschland heute, Kunsthalle, Köln, 14. Februar bis 18. Mai 1970
boek
Keywords: Duitsland